EAST ASIA REGIONAL LEADERSHIP DYNAMIC IN MEGA-REGIONAL AGREEMENT ERA (Dinamika Kepemimpinan Regional Asia Timur Dalam Era Perjanjian Mega-Regional) - Anggara Raharyo; Sheiffi Puspapertiwi (Sekretariat Jenderal DPR RI, 2018)
Mega-regional has become a major trend of the global political economy in this contemporary era. The most talked mega-regional negotiations are centered in East Asia, where Regional Comprehensive Economic Partnership (RCEP) and Trans-Pacific Partnership (TPP) seemed to be contested toward each other. The two mega-regional negotiations promised solution and advancement from stagnant multilateralism and regional trade agreement redundancy. Both regimes also promised possibility for East Asia regionalism, as an inevitable consequence of deeper integration created by the two regimes. Regional leadership is thus becoming a prominent issue, as great powers such as Japan, China, and ASEAN, will struggle to become a regional leader. While participating countries are motivated to conclude negotiation, a major event occurred with the withdrawal of the US from TPP and the establishment of its successor, Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP). This study is aimed to understand East Asia political economy leadership constellation, regarding the current development of mega-regional trade agreements involving the region. We use “leadership” and “regional leadership” as our conceptual frameworks. We use the qualitative method in our study, in which data is obtained from the latest journals and books through literature review. Based on our analysis, we argue that this major shock event has created disruption in East Asia Regionalism, as it provided a new playing field for Japan, changing the balance of regional leadership. To conclude our study, we also propose scenarios for each East Asia great power as an initial discussion responding to this changing event. AbstrakMega regional telah menjadi tren utama dalam politik ekonomi era kontemporer. Negosiasi mega regional yang banyak diperbincangkan berpusat pada Asia Timur, di mana Regional Comprehensive Economic Partnership (RCEP) dan Trans Pacific Partnership (TPP) dikontestasikan dengan satu sama lain. Keduanya menjanjikan solusi dan peningkatan dari stangnansi multilateralisme dan redundansi perjanjian perdagangan regional. Keduanya juga menjanjikan kemungkinan regionalism di Asia Timur, sebagai konsekuensi yang tidak dapat dihindari dari integrasi yang intensif dari kerangka rezim yang ada. Kepemimpinan regional kemudian menjadi isu yang penting, karena kekuatan besar seperti Jepang, China, dan ASEAN akan mencoba untuk menjadi pemimpin kawasan. Di tengah negosiasi negara peserta untuk segera menyelesaikan negosiasi panjang RCEP, peristiwa penting terjadi di mana AS mundur dari TPP serta dibentuknya Comprehensive and Progressive Agreement for Trans Pacific Partnership (CPTPP) sebagai penggantinya. Tulisan ini bertujuan untuk memahami konstelasi kepemimpinan ekonomi politik Asia Timur, dikaitkan dengan perkembangan dari perjanjian perdagangan mega-regional yang melibatkan kawasan ini. Kami menggunakan konsep “kepemimpinan” dan “kepemimpinan kawasan” sebagai kerangka konseptual dalam tulisan ini. Metode kualitatif digunakan dalam studi ini dengan data yang diperoleh dari jurnal terbaru dan buku melalui studi literatur. Berdasarkan analisa yang dilakukan, kami berargumen bahwa peristiwa ini telah menciptakan disrupsi terhadap regionalism Asia Timur, di mana peristiwa tersebut menciptakan arena yang baru bagi Jepang, sehingga mengubah keseimbangan dinamika kepemimpinan regional. Sebagai akhir dari studi yang kami lakukan, selanjutnya kami menawarkan skenario bagi tiap kekuatan besar Asia Timur, membuka diskusi awal sebagai respon dari peristiwa yang terjadi.